RANCANGBANGUN WEB EVALUASI PELATIHAN DI WIKA BETON MAJALENGKA MENGUNAKAN METODE WATERFALL - Qorahman, Opik; Nurdiana, Nunu (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
PT.WIJAYA KARYA MAJALENGKA often conducts training for its employees to improve their understanding of the latest knowledge related to their field. Training evaluations already exist, but they have not been digitized and are only in the form of paper surveys, which often result in damaged files, lost files, sorting errors, and delays that affect the speed of survey data and training certificate production. Due to these problems, an application is needed that can automatically manage survey data and create certificates, which can minimize errors from the limitations of paper-based survey evaluations in the creation of survey data and certificates. The method used is Waterfall, which applies a methodical and sequential approach, with stages that include requirements, design, implementation, verification, and maintenance. The creation of this web application simplifies and accelerates the e-certificate generation process, enabling it to be produced automatically. Additionally, this application provides a feature that allows certificates to be accessed and downloaded, and the application will be equipped with a survey data processing system that enables test results and survey results to be converted into Excel files.